Improvement of Direct Learning Model Using Calculator on Mathematics Learning Achievement of Roving Material and Flat Area in Grade IV Elementary School - Dindi Anovia; Wakhudin Wakhudin; Nur Fajriyah Febrianti (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
This study aims to determine whether the results of learning achievement of students who apply to learning using a direct learning model using a calculator obtain better results than classes that apply to learning using conventional models. This research is quasi-experimental research using a pretest-posttest control group design. The population in this study was the fourth grade of SD UMP, Kembar sub-district, Banyumas Regency, in 2020, which amounted to 59 students. The sample in this study is class IV A, totalling 29 students, and class IV B, totalling 30 students. Class IV A is an experimental class using the application of learning with direct learning models. Class IV B is a control class using the application of direct learning models without a calculator. The sampling technique used is cluster random sampling. The data collection technique in this study was a test in the form of a description, namely pretest and posttest. The results of nonparametric test calculations in u-test Ho are rejected, and Ha is accepted. The results of calculations using SPSS obtained sig < 0.05 or sig 0.001 < 0.05, so there was a significant difference between the experimental class and the control class. Based on the results obtained from the data, it can be concluded that the direct learning model uses a calculator to measure mathematics learning achievement in the material of circumference and area of flat shapes in grade IV elementary school.